2018
DOI: 10.1007/s00348-018-2501-8
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding from tandem cylinders

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. and St is discussed based on shear-layer velocity, approaching velocity, vortex formation length, and wake width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 41 publications
4
19
1
Order By: Relevance
“…For subcritical Reynolds numbers, these phenomena can be explained by the existence of different modes or states of the flow topology and vortex shedding. (Zdravkovich 1987) and (Alam et al 2018) characterized the different states as follows: there are three basic types of the flow structure possible, namely "extended-body regime", "reattachment regime" and "co-shedding regime". In the first regime, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For subcritical Reynolds numbers, these phenomena can be explained by the existence of different modes or states of the flow topology and vortex shedding. (Zdravkovich 1987) and (Alam et al 2018) characterized the different states as follows: there are three basic types of the flow structure possible, namely "extended-body regime", "reattachment regime" and "co-shedding regime". In the first regime, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the negative C p is also observed in the region of near the upstream wall of the first building, however closer to the left corner. The further increase in AOA would lead to the situation when both objects are located side by side with respect to the flow, and such situation well were described in number of previous works [55][56][57]. It can be concluded that the flow pattern varies drastically as the angle of inflow increase, which must consequently affect the pressure loads of objects.…”
Section: Numerical Results Of Pressure Loads On Buildings In Tandem Amentioning
confidence: 54%
“…Whereas a large amount of studies have been performed in the past regarding the fluid-dynamic behaviour of two 2D (i.e. "infinite") smooth circular cylinders (Zdravkovich, 1977;Okajima, 1979;Igarashi, 1981;Pearcy et al, 1982;Arie et al, 1983;Igarashi, 1984;Zdravkovich, 1985Zdravkovich, , 1987Meneghini et al, 2001;Alam et al, 2003;Zhou and Yiu, 2006;Alam and Zhou, 2007;Carmo et al, 2010;Sumner, 2010;Alam and Meyer, 2011;Alam, 2014;Griffith et al, 2017;Alam et al, 2018;Schewe and Jacobs, 2019;Hosseini et al, 2021;Schewe et al, 2021) or sharp-edged prisms with square cross sections (Reinholds et al, 1977;Shiraishi et al, 1986;Kareem, 1987;Sakamoto et al, 1987;Sakamoto and Haniu, 1988;Luo, 1989;Luo and Teng, 1990;Ohya et al, 1989;Luo and Teng, 1990;Takeuchi and Matsumoto, 1992;Tatsutani et al, 1993;Hangan and Vickery, 1999;Luo et al, 1999;Alam et al, 2002;Liu and Chen, 2002;Kim et al, 2008;Yen et al, 2008;Sohankar and Etminan, 2009;Etminan et al, 2011;…”
Section: Two Square-section Prisms With Finite Edge Roundness Arrange...mentioning
confidence: 99%